2022
DOI: 10.1111/jocs.16514
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus 2019 (COVID‐19) venovenous extracorporeal oxygenation: Single community hospital results and insights

Abstract: Background The role of extracorporeal membrane oxygenation (ECMO) for patients with refractory respiratory failure due to coronavirus 2019 (COVID‐19) is still unclear even now over a year into the pandemic. ECMO is becoming more commonplace even at smaller community hospitals. While the advantages of venovenous (VV) ECMO in acute respiratory distress syndrome (ARDS) from COVID‐19 have not been fully determined, we believe the benefits outweighed the risks in our patient population. Here we describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Although some patients with MIS-C recovered promptly and were decannulated within 1 week after venoarterial-ECMO initiation ( 11 , 13 , 29 , 33 , 34 , 39 , 51 , 52 , 54 ), one patient with ARDS remained on venovenous-ECMO for 71 days ( 35 ). It is not uncommon that pulmonary function takes a month or more to recover in adult COVID-19 cases as well ( 67 , 68 ). In the face of critically ill children with COVID-19 necessitating ECMO support, recognizing the difference in possible recovery timelines according to ECMO indications and modes will play a crucial role in assessing the treatment courses appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…Although some patients with MIS-C recovered promptly and were decannulated within 1 week after venoarterial-ECMO initiation ( 11 , 13 , 29 , 33 , 34 , 39 , 51 , 52 , 54 ), one patient with ARDS remained on venovenous-ECMO for 71 days ( 35 ). It is not uncommon that pulmonary function takes a month or more to recover in adult COVID-19 cases as well ( 67 , 68 ). In the face of critically ill children with COVID-19 necessitating ECMO support, recognizing the difference in possible recovery timelines according to ECMO indications and modes will play a crucial role in assessing the treatment courses appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the format of the transfer of care model espoused by the CESAR trial has become flawed due to this sudden change in the ARDS incidence, resulting in a saturation of resources of the specialized referral healthcare systems. West et al, in their study, have nicely shown how high‐quality ECMO can be done beyond the confines of a specialized, large healthcare system, thus meeting this new challenge posed by the COVID‐19 pandemic 3 …”
Section: Commentarymentioning
confidence: 99%
“…West et al, in their study, have nicely shown how high‐quality ECMO can be done beyond the confines of a specialized, large healthcare system, thus meeting this new challenge posed by the COVID‐19 pandemic. 3 …”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the format of the transfer of care model espoused by the CESAR trial has become flawed due to this sudden change in the ARDS incidence, resulting in a saturation of resources of the specialized referral healthcare systems. West and colleagues, in their study, have nicely shown how high-quality ECMO can be done beyond the confines of a specialized, large healthcare system, thus meeting this new challenge posed by the COVID-19 pandemic 3 .…”
mentioning
confidence: 99%